Restoration of quarry areas in Mediterranean regions through a low-cost soil rebuilding technique for profitable pedotechnosystems development - Grilli, Eleonora; Vigliotti, Renata Concetta; Rossetti, Luigi; Scognamiglio, Monica; Fiumano, Vittorio; Fiorentino, Antonio; Leone, Natalia; Nogueira, Thiago Assis Rodrigues [UNESP]; Abreu-Junior, Cassio Hamilton; Jani, Arun Dilipkumar; Capra, Gian Franco; Ganga, Antonio (Elsevier, 2021)
Exploitation of tuff deposits represents an intensive and destructive human activity that can completely modify natural soils, sometimes leading to their total disappearance. Soil reclamation of quarry areas can usually be done by soil rebuilding, employing complex and expensive techniques. In this research, we aimed to evaluate reconstructed Technosols and associated vegetation, called pedotechnosystem (PTS) and their development and behaviour for tuff quarry reclamation for both environmental rehabilitation and agricultural purposes. Technosols were investigated under three different conditions: i) a control consisting of a constructed Technosol (CT) without additional treatments; ii) CT treated with conventional mineral fertilization (CTCF); and, iii) CT treated with a composted mix of commercial organic amendments (CTOA). Different open-air mesocosms (pots) were investigated and evaluated in terms of: i) development, production, and metabolomic profile of rosemary (Rosmarinus officinalis L.), olive (Olea europaea L.), and grapevine (Vitis Vinifera L. ssp. Sativa) in a mixture with a pasture species: ii) the Technosols physical-chemical responses. Specifically, after 15 months, all investigated PTS were evaluated in terms of: i) pasture species total dry matter (TDM) production, height (H), stem diameter (D) and nitrogen (N), phosphorus (P), and potassium (K) content of dry matter; ii) physical-chemical analyses of all investigated substrates; iii) olive, grape, and rosemary characterization by analysing N, P, and K content in dry leaves as well as their metabolomic profile. Statistical differences among treatments were ascertained through ANOVA, while observed variability was interpreted using a principal factor analysis (PFA). Use of CTOA resulted in statistically (p < 0.05) higher performances in terms of TDM as well as P contents in harvested pasture species. In CTOA, more favourable pH conditions (near neutral) for plant growth were observed; additionally, such PTS showed the best performances in terms of soil organic matter (SOM), total N, and P as well as an improvement for most of the investigated organic fractions and relative humification indexes. Identified metabolites varied greatly by species, underscoring the capability of metabolites in fingerprinting different species and related responses to environmental stress factors. Results from PFA showed that: i) CTOA produced better growing conditions and agronomic performance among all investigated PTS; ii) metabolomic profiles are a reliable fingerprint for investigating plant responses to environmental stress and can help differentiate behaviour that follows. Overall, the research demonstrated that CTOA represents a low-cost easily applicable technique for soil rebuilding in tuff quarry areas.
Keywords: Agricultural reconversion; Mesocosms; Metabolomic profiles; Multivariate statistics; Technosols